Mengeksplorasi Faktor Pendorong dan Penarik Minat Berwirausaha Mahasiswa: Sebuah Pendekatan Group Model Building - Gani, Ariel Nian; Rofi'i, Muhammad (Lembaga Penelitian Universitas YARSI, 2025)
This study examines the cognitive mechanisms underlying university students’ entrepreneurial intentions by analyzing the interplay of push and pull factors. Using a qualitative system dynamics approach through Group Model Building (GMB), a Causal Loop Diagram (CLD) was co-developed with 13 student-entrepreneurs, identifying fifteen interconnected cognitive drivers shaping entrepreneurial decision-making. The results reveal that pull factors particularly self-fulfillment, perceived opportunity, and supportive environments play a dominant role, while push factors primarily act as triggers that intensify entrepreneurial engagement. The CLD further uncovers reinforcing feedback loops in which entrepreneurial action enhances financial capability, social support, and self-efficacy, thereby sustaining intention over time. From a managerial perspective, the findings suggest that universities and policymakers should design entrepreneurship programs that simultaneously reduce barriers to employment dissatisfaction and strengthen opportunity-driven motivations, supported by experiential learning and ecosystem facilitation. Academically, this study contributes by integrating push–pull theory with cognitive mapping and system dynamics, offering a dynamic, feedback-based explanation of entrepreneurial intention that extends beyond static, variable-centered models.